2013
DOI: 10.1016/j.jacme.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of early mortality in patients with paraquat intoxication

Abstract: Objective: Paraquat intoxication has a high mortality rate. The purpose of this study is to identify the clinical features and predictors of early mortality within 72 hours among individuals with paraquat intoxication in central Taiwan.Methods: This retrospective study included 92 patients who presented with paraquat intoxication at the emergency department (ED) of a medical center between January 2004 and December 2009. The patient characteristics, clinical features and outcomes of these patients are presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
1
7
0
4
Order By: Relevance
“…Table demonstrates the total number and fatality rate data for paraquat poisoning in the 10 countries with the most published papers. Very high fatality rates were in Asia, including Japan (78.6%) and Taiwan (67.4%) . In addition, it is apparent from this table that paraquat is banned in the UK and the Europe countries (France, Germany, Spain, and Italy) since 2007, and in South Korea since 2012 .…”
Section: Resultsmentioning
confidence: 94%
“…Table demonstrates the total number and fatality rate data for paraquat poisoning in the 10 countries with the most published papers. Very high fatality rates were in Asia, including Japan (78.6%) and Taiwan (67.4%) . In addition, it is apparent from this table that paraquat is banned in the UK and the Europe countries (France, Germany, Spain, and Italy) since 2007, and in South Korea since 2012 .…”
Section: Resultsmentioning
confidence: 94%
“…1 ). Ten studies were published in English [ 8 , 11 , 19 26 ] and 19 studies were published in Chinese, [ 27 – 45 ] as shown in Table 1 . Twenty-seven studies were conducted in Chinese and 2 studies in Korean.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of PQ intoxication has evolved over years, and this might have affected the observed outcomes. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If not regulated properly, the excess ROS can impair the cellular lipids, proteins, and/ or DNA, inhibiting their normal functions [5]. The secondary effects of oxidative stress include lipid peroxidation, mitochondrial toxicity, oxidation of Nicotinamide Adenine Dinucleotide Phosphate (NADP), apoptosis and activation of nuclear factor kappa B [6]. These effects induce the formation of inflammatory enzymes, cytokines, and chemokines.…”
Section: Introductionmentioning
confidence: 99%